Synthesis and LPG sensing properties of nano-sized cadmium oxide - Waghulade, R. B.; Patil, P. P.; Pasricha, Renu (Talanta, 2007)
This paper reports the synthesis and liquid petroleum gas (LPG) sensing properties of nano-sized cadmium oxide (CdO). The nano-sized CdO powder was successfully synthesized by using a chemical co-precipitation method using cadmium acetate and the ammonium hydroxide, as starting materials and water as a carrier. The resulting nano-sized powder was characterized by X-ray diffraction (XRD) measurements and the transmission electron microscopy (TEM). The LPG sensing properties of the synthesized nano-sized CdO were investigated at different operating temperatures and LPG concentrations. It was found that the calcination temperature and the operating temperature significantly affect the sensitivity of the nano-sized CdO powder to the LPG. The sensitivity is found to be maximum when the calcination temperature was 400 degrees C. The sensitivity to 75 ppm of LPG is maximum at an operating temperature 450 degrees C and it was found to be similar to 34 1 %. The response and recovery times were found to be nearly 3-5s and 8-10s, respectively. The synthesized nano-sized CdO powder is able to detect up to 25 ppm for LPG with reasonable sensitivity at an operating temperature 450 degrees C and it can be reliably used to monitor the concentration of LPG over the range (25-75 ppm). The experimental results of the LPG sensing studies reveal that the nano-sized CdO powder synthesized by a simple co-precipitation method is a suitable material for the fabrication of the LPG sensor. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chemical co-precipitation; Gas sensor; LPG; nano-sized CdO

Gas sensing properties of magnesium ferrite prepared by co-precipitation method - Hankare, P. P.; Jadhav, S. D.; Sankpal, U. B.; Patil, R. P.; Sasikala, R.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2009)
Polycrystalline magnesium ferrite (MgFe(2)O(4)) was prepared by the co-precipitation method. The synthesized compound was characterized for their phase and morphology by X-ray diffraction and scanning electron microscopy, respectively. Conductance responses of the (MgFe(2)O(4)) were measured towards gases like hydrogen sulfide (H(2)S), liquefied petroleum gas (LPG), ethanol vapors (C(2)H(5)OH), SO(x), H(2), NO(x), NH(3), methanol, acetone and petrol. The gas sensing characterstics were obtained by measuring the sensitivity as a function of various controlling factors like operating temperatures and concentrations of gases. It was found that the sensor exhibited various responses towards these gases at different operating temperatures. Furthermore; the MgFe(2)O(4) based sensor exhibited a fast response and a good recovery towards petrol at temperature 250 degrees C. The results of the response towards petrol reveal that (MgFe(2)O(4)) synthesized by a simple co-precipitation method, would be a suitable material for the fabrication of the petrol sensor. (C) 2009 Published by Elsevier B.V.
Keywords: Ferrites; Gas sensor; X-ray diffraction and scanning electron microscopy

Liquefied petroleum gas sensing performance of cerium doped copper ferrite - Khandekar, M. S.; Tarwal, N. L.; Patil, J. Y.; Shaikh, F. I.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2013)
Undoped and cerium (Ce) doped nanocrystalline copper ferrite (CuFe2O4) materials were synthesized via the molten-salt (M-S) method. Effects of Ce doping on the structural, morphological and gas sensing properties of the CuFe2O4 ferrite have been investigated. X-ray diffraction (XRD) analysis revealed the formation of spinel CuFe2O4. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) investigations showed that the synthesized ferrite is made up of very fine spherical nanoparticles. Moreover, the gas sensing properties of sintered samples were studied towards different reducing gases such as liquefied petroleum gas (LPG), acetone, ethanol and ammonia. The sample with 4% cerium doped CuFe2O4 (Ce4) showed the maximum gas sensitivity (86%) towards LPG with fast response time of 5 s and good recovery time of 68 s. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ferrite; Gas sensor; Molten-salt method; TEM

Nanocrystalline Ce doped CoFe2O4 as an acetone gas sensor - Khandekar, M. S.; Tarwal, N. L.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2014)
Nanocrystalline CoFe2-xCexO4 ferrites (x=0, 0.04, 0.08) were synthesized by using the inexpensive, simple and eco-friendly molten-salt (M-S) method. Effects of Ce doping on the structural, morphological and gas sensing properties of the CoFe2O4 ferrite were investigated. X-ray diffraction (XRD) analysis revealed the formation of spinel CoFe2O4. Transmission electron microscopy (TEM) investigations showed that the synthesized ferrite is made up of very fine spherical nanoparticles. Furthermore, the gas response of nanocrystalline ferrite materials was investigated in the temperature range of 200-450 degrees C toward the reducing gases like liquefied petroleum gas (LPG), acetone, ethanol and ammonia. The sensor response was found to be sensitive and selective toward acetone as compared to other reducing gases. It is observed that the addition of Ce (4 wt%) strongly influenced the response and the operating temperature of the sensor material and thus can serve as acetone-sensing sensors. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: CoFe2O4; Ferrite; Gas sensor; Molten-salt method; TEM

Effect of Pd and Ce on the enhancement of ethanol vapor response of SnO2 thick films - Bagal, L. K.; Patil, J. Y.; Vaishampayan, M. V.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Sensors and Actuators B-Chemical, 2015)
The undoped SnO2 and 4 wt% Ce-doped SnO2 were successfully synthesized by a facile co-precipitation route. The ternary systems were prepared by Pd-loading (0.5, 1.5 and 3.0 wt%) on the 4 wt% Ce-doped SnO2 nanoparticles. The structure and morphology of the nanocrystalline powders were investigated by X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques. The nanocrystalline powders were screen printed on the alumina substrates to form thick films to investigate their gas response properties. The gas response studies reveal that 4 wt% Ce-doped SnO2 with the loading of 3.0 wt% Pd exhibits high response (88%) towards ethanol (100 ppm) at an operating temperature of 250 degrees C with quick response (6 s) and rapid recovery (20 s). The high ethanol vapor response at lower operating temperature of this sensor is attributed to the spill-over mechanism of Pd particles present on the SnO2 surface and enhancement in alkalescence of SnO2 due to Ce-doping. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ce-doped tin oxide; Gas sensor; Semiconductor; Thick film